Behaviour and ultimate strength of continuous steel plates subjected to uniform transverse loads - Ratzlaff, K. P.; Kennedy, D. J. L. (Canadian Journal of Civil Engineering, 1986)
The authors previously established that an initially flat rectangular steel plate, clamped on all four edges, displays three modes of behaviour as the intensity of a distributed transverse load increases: elastic flexural-membrane action, inelastic flexural-membrane action, and inelastic-membrane action.For a long narrow plate, elastic flexural-membrane action exists up to the load at which yielding of the extreme fibres along the long edges occurs. Subsequent plastic hinge formation along the long edges reduces the stiffness. The second stage ends with complete yielding in tension along the long edges. From this point onward, the plate acts essentially as a membrane straining inelastically as yielding gradually progresses from both edges toward the centre. A lower bound to this behaviour is obtained by assuming that Poisson's ratio is the elastic value and the maximum membrane stress is the yield stress. A higher lower bound is obtained using the plastic value of Poisson's ratio. The load–deflection curve gradually moves from the lower value to the higher and, because the edge forces can exceed yield, will finally exceed the latter, as confirmed by tests.A finite element program modelling plane stress conditions, the inelastic Poisson's ratio, and the stress–strain behaviour to failure gave a load–deflection response closely following the three predicted regions of behaviour. Two failure criteria have been established: a limiting tensile strain due to bending and tension at the edge and the shear resistance there. The behaviour and failure loads have been confirmed by two tests. Strain measurements taken during the tests substantiate, in general, the predicted behaviour.Implications of using the ultimate strength of plates for the design of offshore structures for oil exploration and production in the Arctic are presented. Key words: deflection, design, finite elements, inelastic, membrane, plates, steel, strains, stresses, transverse load, ultimate strength.